Building the Soul of the Indonesian Nation: Mohammad Hatta on Religion, the State Foundation, and Character Building - Latif, Yudi (Studia Islamika, 2025)
Mohammad Hatta (1902–1980), Indonesia’s first Vice President and co-proclaimer of independence, was also an intellectual statesman, economist, educator, and prolific writer. This essay explores Hatta’s vision of nurturing the moral and spiritual soul of the nation—encompassing mental-spiritual development, national character, and public morality—through his writings and speeches on religion, statehood, education, culture, and nationhood from the 1930s to the 1970s. His religious outlook was substantive and inclusive, emphasizing shared values across faiths. This enabled a balanced view of religion’s public role, transcending the dichotomy of ‘integration’ and ‘separation’, and anticipating José Casanova’s and Alfred Stepan’s concept of ‘differentiation’. Hatta stressed character education and human capability as the foundations of a sovereign, just, and prosperous Indonesia based on Pancasila. His notion of progress—focused on improving quality of life and human capabilities through education and health—preceded the human development framework later developed by Amartya Sen. He emphasized the integration of intellectual excellence and moral integrity to build a dignified nation with a noble national character.